What it takes to do it right: an integrative EMT-based model for legal translation competence - Federica Scarpa; Daniele Orlando (JoSTrans: The Journal of Specialised Translation)
Over the past few decades, research has yielded valuable models for the conceptualisation of translation competence, both in the academic and professional worlds (Göpferich 2009; Kelly 2002; PACTE 2003). However, despite the growing consensus on translation competence as a multi-faceted competence comprising several core skills, the different perspectives have resulted in terminological (when not downright conceptual) ambiguity. This paper aims to investigate in a didactic perspective the specific competences and sub-competences required for translating legal documents, with particular reference to the focus of the QUALETRA2 project, i.e. the specific skills required for translating criminal proceedings, in line with Directive 2010/64/EU. Informed by both recent research (cf. Prieto Ramos 2011; Piecychna 2013) and the outcomes of recent EU projects, as well as by the principle that a legal translator is first a translator (Cao 2007: 39), the proposed model is based on the general EMT reference framework for translation competences (EMT Expert Group 2009a: 3), which has been integrated with additional core components that are more strictly related to legal translation. The model is then contrasted with the results of three recent surveys on translation competence (Chodkiewicz 2012; OPTIMALE 2013; Orlando and Scarpa 2014). It will be finally argued that such an integrative approach has direct implications for training translators of criminal proceedings and can be adopted as a basis to assess and certify the competences and skills of prospective translators in this specific legal subdomain.